2008
DOI: 10.1021/la800333g
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3,4-ethylenedioxythiophene) (PEDOT) Nanobiointerfaces: Thin, Ultrasmooth, and Functionalized PEDOT Films with in Vitro and in Vivo Biocompatibility

Abstract: Nanobiointerfaces were prepared based on an electrically conductive polyethylenedioxythiophene (PEDOT). Thin (<100 nm), ultrasmooth (roughness ( R(rms)) < 5 nm), and functionalized PEDOT films have been successfully electropolymerized using aqueous microemulsion. The microemulsion polymerization is found to be catalyzed in the presence of a low concentration of acid and allows for film formation from various functionalized ethylenedioxythiophenes (EDOTs) (e.g., EDOT-OH, C(2)-EDOT-COOH, C(4)-EDOT-COOH, C(2)-EDO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
211
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 303 publications
(217 citation statements)
references
References 61 publications
4
211
0
2
Order By: Relevance
“…EDOT-OH was purchased from a custom-synthesis company, where it had been prepared following procedures previously reported 66,67 . EDOT-COOH was synthesized following procedures previously reported 68,69 . 2-Maleimidoethylamine hydrochloride and 1-ethyl-3-(3-dimethyaminopropyl)-carbodiimide hydrochloride were purchased from Astatech and Tokyo Chemical Industry, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…EDOT-OH was purchased from a custom-synthesis company, where it had been prepared following procedures previously reported 66,67 . EDOT-COOH was synthesized following procedures previously reported 68,69 . 2-Maleimidoethylamine hydrochloride and 1-ethyl-3-(3-dimethyaminopropyl)-carbodiimide hydrochloride were purchased from Astatech and Tokyo Chemical Industry, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Valle et al (2007) investigated the interaction of PEDOT films with epithelial cells and showed the biocompatibility of PEDOT with epithelial cells. Luo et al (2008) synthesized PEDOT films and investigated their biocompatibility by seeding NIH3T3 fibroblasts on PEDOT films, and carried out subcutaneous implantation of PEDOT films by in vivo study. Their results showed that PEDOT films exhibit very low intrinsic cytotoxicity and that their inflammatory response upon implantation was good, making them ideal for biosensing and bioengineering applications.…”
Section: Poly (3 4-ethylenedioxythiophene)mentioning
confidence: 99%
“…Poly(3,4-ethylenedioxythiophene) (PEDOT) is a biocompatible CP which is recently being employed in biomedical applications, 22 especially in nerve tissue engineering. 23 To gain a water soluble polyelectrolyte system with good film-forming properties, PEDOT is doped with poly(4-styrenesulfonate) (PSS).…”
Section: Introductionmentioning
confidence: 99%